2021
DOI: 10.31234/osf.io/3df57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of motor inhibition during covert speech production

Abstract: Covert speech is accompanied by a subjective multisensory experience with auditory and kinaesthetic components. An influential hypothesis states that these sensory percepts result from a simulation of the corresponding motor action that relies on the same internal models recruited for the control of overt speech. This simulationnist view raises the question of how it is possible to imagine speech without executing it. In this perspective, we discuss the possible role(s) played by motor inhibition during covert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Results from this analysis showed that motor inhibition may have different effects on patterns of RTs and MTs, suggesting that it may affect different aspects of the latent activation function (i.e., the shape of the activation function or the motor execution threshold). More precisely, the shortening of RTs (jointly observed with the lengthening of MTs) following imagined trials is compatible with a decrease in the motor execution threshold (as reported in Table 3), whereas the lengthening of both RTs and MTs following imagined trials (as observed in previous studies) is compatible with a delay in the peak time of the activation function (as previously suggested by Nalborczyk et al, 2024).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Results from this analysis showed that motor inhibition may have different effects on patterns of RTs and MTs, suggesting that it may affect different aspects of the latent activation function (i.e., the shape of the activation function or the motor execution threshold). More precisely, the shortening of RTs (jointly observed with the lengthening of MTs) following imagined trials is compatible with a decrease in the motor execution threshold (as reported in Table 3), whereas the lengthening of both RTs and MTs following imagined trials (as observed in previous studies) is compatible with a delay in the peak time of the activation function (as previously suggested by Nalborczyk et al, 2024).…”
Section: Discussionsupporting
confidence: 87%
“…Parameter estimates obtained by fitting the algorithmic model to these data suggest that these differences may be due to different underlying inhibitory mechanisms. More precisely, the shortening of RTs (jointly observed with the lengthening of MTs) following imagined trials is compatible with a decrease in the motor execution threshold (as reported in Table 3), whereas the lengthening of both RTs and MTs following imagined trials is compatible with a delay in the peak time of the activation function (as previously suggested by Nalborczyk et al, 2024).…”
Section: Modelling Latent Inhibitory Processessupporting
confidence: 82%
See 3 more Smart Citations